Implementasi Pendidikan Agama Islam Berbasis Nilai Multikultural Dalam Membentuk Karakter Peserta Didik Pada Smk Kesehatan Hamzar Bayan Lombok Utara - Kartini; Ramdhani, Deddy (Mu'allim, 2024)
This research aims to describe the methods and impacts of implementing Islamic religious education based on multicultural values in shaping the character of students at the Hamzar Bayan Health Vocational School. This research is a type of qualitative research, namely a research approach that produces descriptive data in the form of data from observations, interviews and documentation. Data analysis was carried out using data reduction, data display and conclusion drawing/verification. The emergence of the idea of a multicultural-based Islamic religious education program in shaping the character of students is highly desired, because so far it has been felt that the educational process has not been successful in developing people with character. It could be that one of the reasons is because education currently focuses more on intellectual or cognitive development alone. Therefore, to realize religious character education for students, schools are needed that do not only pay attention to intellectual or cognitive aspects alone, but also include aspects of soft skills or non-academic as one of the main elements of moral education. Hamzar Bayan Health Vocational School as a vocational high school which is under the auspices of the Marakitta'limat Foundation is considered to be the right place to shape the character of students, through familiarizing students with religious activities which are implemented through daily habits as well as in extra or intra-school activities. This can be seen from multicultural values such as the values of togetherness, diversity and democracy which can be seen in teaching methods, so that it can form students who are not only skilled at working in the health sector but also excel in religious achievements and have good morals.